Penguatan mutu pembelajaran melalui manajemen SDM pendidikan yang profesional untuk bilingual school di Kalimantan Timur - Indri; Laili Komariyah; Yudo Dwiyono (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Introduction: The urgency of research focused on educational human resource management aims to uncover and understand the meaning of experiences of unprofessional educational human resource management that undermine the quality of learning, thereby providing a more comprehensive understanding of the phenomenon of bilingual schools in East Kalimantan. Method: Systematic literature review with keywords relevant to the research focus. Result: By focusing on the meaning of experiences of unprofessional educational human resource management, this research makes a comprehensive contribution. Discussion: A phenomenological approach is relevant and essential because it allows researchers to explore the meaning of experiences of unprofessional educational human resource management into a dimension that cannot be captured by quantitative surveys or structural case studies. As demonstrated in the literature on teacher identity, professional identity is strongly influenced by organizational processes, recruitment, and development. This gap underscores the urgency of in-depth studies to reconstruct an understanding of how professionalism is practiced.